OPTIMIZING STUDENTS READING COMPREHENSION OF DESCRIPTIVE TEXT THROUGH E LEARNING METHOD WITH WHATSAPP APPLICATION AT STUDENTS OF SMA NEGERI 1 BUKO - Tangiduk, Yustira Kharlina; Samola, Nurmin; Rorimpandey, Rinny (Journal of English Culture, Language, Literature and Education, 2021)
This study aims to determine whether the E learning method can be effective in optimizing students reading comprehension of descriptive text with WhatsApp Application This research was conducted in class X MIA 1 SMA Negeri 1 Buko in the academic year of 2020 2021 This study used one group pretest postest design of research with the data analysis was the frequency distribution of scores mean and standard deviation The questions from the pretest and posttest used the type of multiple choice questions with questions about the descriptive text From this result it was found that the mean of posttest Y = 7 8 with standard deviation Sy< sub> = 0 79 was higher than the mean score at pretest X = 5 33 with standard deviation Sx< sub> = 0 89 It means that students reading comprehension in the descriptive text was higher after treatment at posttest than pretest So the researcher concluded that the application of the E learning method through WhatsApp application was effective in optimizing students reading comprehension of descriptive text < p>